Perspective of pediatricians and adolescent patients on the transition process in a university hospital - Luiza Mariana Cordeiro Silva; Letícia Mansano Souza; Elizete Prescinotti Andrade; Lilia D'Souza-Li (Sociedade de Pediatria de São Paulo, 2022)
ABSTRACT Objective: To map the transition process from the perspective of pediatricians and their adolescent patients, and to suggest a transition protocol. Methods: This is a descriptive, cross-sectional study conducted in a pediatric outpatient clinic of a public tertiary hospital. Pediatricians answered a questionnaire about the transition process, and that was evaluated in a descriptive manner. The Transition Readiness Assessment Questionnaire (TRAQ) on health autonomy was answered by the adolescents and the analysis was performed using the χ2 and Mann-Whitney tests. p<0.05 were considered significant. Results: 31 pediatricians (16 residents, 15 supervisors) were enrolled, with a mean age of 40.1 (±16.9), 87% women, with years working in Pediatrics ranging from 2 to 45 years (median of 5 years). Most doctors agreed that there was no transition plan, but they stimulated the patient's autonomy and talked to the patient and family members about any existing chronic diseases. A total of 102 adolescent patients participated, with a median age of 15; 56% were female. The TRAQ median was 58, with similar scores between females and males, and higher scores in those older than 16 years of age (Mann-Whitney U test, p=0.01). The patients reported ease in face-to-face communication with their doctors, but great difficulty in talking about health issues over the phone. Conclusions: Even without a transition protocol, adolescents developed several self-care skills as they aged. The lack of a transitional protocol led to conflicting opinions, which reinforces the need for improvement. We suggest a flowchart and transition protocol.